Rarely seen nasal congenital problems causing neonatal upper respiratory obstruction: a case series - Yeşim Başal; Abdullah Bariş Akcan; Yasemin Durum Polat; Ceren Günel; Aylin Eryilmaz; Sema Başak (MDPI AG, 2016)
Since newborns are obligatory nasal breathers, upper respiratory tract problems may sometimes be life threatening. The most common pathology causing dyspnea and stridor in newborns is laryngomalacia. Nasal cavity pathologies that risk the neonatal airway are more rarely met. These anomalies may be seen either as solitary anomalies or as a part of a syndrome. While choanal atresia is one of the best-known nasal cavity anomalies, choanal stenosis, congenital nasal mid-line masses, congenital nasal pyriform aperture stenosis, and nasal tip anomalies are more rarely seen structural pathologies. Choanal atresia may be present either as an isolated congenital anomaly or as a part of CHARGE syndrome. Some rare chromosome anomalies may also cause significant problems during nasal respiration in newborns. With this study, we presented a case series of newborns with pathologies that affected nasal respiration. Although the diagnosis and treatment of choanal atresia and congenital dacryocystocele are well known, the information on the diagnosis and treatment of the other two uncommon cases are limited. With this study, we aimed to contribute to the literature by presenting our approach in six cases having congenital pathologies that cause nasal respiratory obstruction.